Gender Differences and Peer Pressure as Correlates of Psychological Wellbeing of Senior Secondary School Adolescents in North-West, Nigeria - ALHASSAN, Ahmed; AMINU-MASKA, Maryam; IBRAHIM, Bara’atu (Ilorin Journal of Education, 2024)
This study examined gender differences and peer pressure as correlates of the psychological well of senior secondary school adolescents in north-west, Nigeria. The study employs a correlational research design. Six schools were randomly selected from the target population of three hundred and seven thousand, one hundred and eight (307,108) students; 384 students were selected to make the sample for the study. The study adapted Peer Pressure Scale (PPS) by Santor, Messervey and Kusumakar, (2000). and Psychological Well-being Scale (PWS) by Carol D. Ryff (2007) at 0.82, and 0.88 reliability coefficients, respectively. The statistic used for data analysis was the PPMC. Three hypotheses were tested at 0.5 level of significance. The results showed that: H01: reveals a positive correlation (r-value of .658*) which is significant at 0.05 alpha levels of significance (r = .658, p < 0.05), null hypothesis 2 presents t-value of -.027, df 382, p=.979. Thus, the null hypothesis is accepted. While the null hypothesis 3 result showed that t=1.439; df =382, p> 0.05 and the hypothesis is retained, it is therefore recommended that trained counselor should be sent to each secondary school to assist in the counseling of a few teenagers who are subjected to negative peer pressure. Parents should also provide adequate monitoring and not allow other factors in the home environment to distract their children. Furthermore, parents are encouraged to provide the right education they can afford for their children irrespective of gender.